Household Income Inequality of Fishermen in Sungai Kakap Village, Kubu Raya Regency, West Kalimantan) (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
Income inequality of fishermen’s households reflects the distribution of income among families who depend on the fisheries sector as their main source of livelihood, as well as additional income from other sectors that have the potential to create economic inequality or equality. This study aims to analyze the distribution of income of fishermen's households in Sungai Kakap Village, Sungai Kakap District, Kubu Raya Regency, West Kalimantan. The method applied in this study is descriptive with a quantitative approach. The research sample consisted of 90 fishermen's households in Sungai Kakap Village. The income of fishermen's households in Sungai Kakap Village is significantly influenced by seasonal changes in fishing activities, which are divided into two periods, namely the harvest season (April-September) and the lean season (October-March). To measure income inequality, the Gini Coefficient and Lorenz Curve are used. Based on the results of the Gini Ratio calculation, the distribution of income of fishermen's households in Sungai Kakap Village has a value of 0.184, which indicates a low level of inequality so that it is known that the income of the fishermen community in Sungai Kakap Village is almost evenly distributed by working as fishermen.